Island blues: indigenous knowledge of indigo-yielding plant species used by Hainan Miao and Li dyers on Hainan Island, China - Libin Zhang; Lu Wang; Anthony B. Cunningham; Yuru Shi; Yuhua Wang (BMC, 2019)
Abstract Background Historically, indigo-yielding plant species were important cash crops from Central Asia to the southern United States and Central America. Indigo-dyed textiles were widely traded along the legendary Silk Road that linked China to Europe. Today, due to the labor-intensive nature of indigo extraction at the household level, lifestyle changes and the widespread availability of commercially produced indigo paste, traditional indigo extraction methods have declined in villages. Yet Li textile weavers on Hainan Island are internationally recognized as producers of indigo-dyed textile using warp ikat techniques. In contrast, Hainan Miao weavers produce indigo-dyed textiles using batik (wax resist) techniques. The aim of this study was to document the indigenous knowledge on indigo-yielding plant species used by both Hainan Miao and Li people on Hainan Island, China. Method Ethnic uses were documented during three field surveys, through a questionnaire survey of 193 respondents, comprising 144 Hainan Miao and 49 Li traditional dyers. Mention index (QI), Availability index (AI), and Preference ranking (PR) of each indigo-yielding plant species were calculated to screen out plant resources with potential development value. Results Five indigo-yielding plant species (from four plant families and four genera) were historically used by Hainan Miao and Li dyers. However, just four species are still in use. Strobilanthes cusia was the main indigo source for Hainan Miao dyers. Li dyers also commonly use Indigofera species (I. tinctoria and I. suffruticosa) for indigo extraction. Wrightia laevis is less commonly used as a contemporary indigo source. Indigo extraction by steeping in water to which lime is added to increase the pH is sharing by the five indigo-yielding plant species. Strobilanthes cusia had the highest QI, AI and PR values in Hainan Miao villages. Indigofera tinctoria had the highest QI and AI values, but Indigofera suffruticosa was preferred by Li dyers. Conclusion In the process of modernization and urbanization, some Hainan Miao and Li dyers retain the traditional indigo extraction methods. We found that Strobilanthes cusia and Indigofera tinctoria have the most potential for sustainable indigo production in the future. Furthermore, this study documents the details of extraction method from Wrightia laevis for the first time and the use of Ricinus communis seeds in that process. As one of the last places globally where Wrightia laevis is still used for indigo production, the may also be a nice market among textile collectors and museums that keeps the tradition of Wrightia laevis production and use for indigo extraction alive.